2012
DOI: 10.1021/jp3085099
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Reactions and Mechanism of Glucose Pyrolysis and Implications for Cellulose Kinetics

Abstract: Concerted reactions are proposed to be keys to understanding thermal decomposition of glucose in the absence of ionic chemistry, including molecular catalysis by ROH molecules such as H(2)O, other glucose molecules, and most of the intermediates and products. Concerted transition states, elementary-reaction pathways, and rate coefficients are computed for pyrolysis of β-D-glucose (β-D-glucopyranose), the monomer of cellulose, and for related molecules, giving an improved and elementary-reaction interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
221
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(241 citation statements)
references
References 53 publications
20
221
0
Order By: Relevance
“…One reason for the lack of LGA formation in our simulations may be the high temperatures, which could lead to radical chemistry dominating over the concerted routes to LGA. Another factor may be the absence of the chemical and electrostatic environment of crystalline (or amorphous) cellulose, especially since the presence of hydroxyl groups on neighbouring chains has been proposed to catalyse concerted reactions (Assary and Curtiss 2012;Seshadri and Westmoreland 2012).…”
Section: Depolymerisation Reactionsmentioning
confidence: 99%
“…One reason for the lack of LGA formation in our simulations may be the high temperatures, which could lead to radical chemistry dominating over the concerted routes to LGA. Another factor may be the absence of the chemical and electrostatic environment of crystalline (or amorphous) cellulose, especially since the presence of hydroxyl groups on neighbouring chains has been proposed to catalyse concerted reactions (Assary and Curtiss 2012;Seshadri and Westmoreland 2012).…”
Section: Depolymerisation Reactionsmentioning
confidence: 99%
“…Glucose, a monomer of cellulose, is the most common of them all. Seshadri and Westmoreland (2012) investigated the pyrolysis of beta-D-glucose and pathways for reactions such as dehydration, retro-aldol condensation and keto-enol tautomerization were proposed. Their studies suggested that bimolecular mechanisms, involving a water molecule or a neighboring R-OH molecule, have a lower activation energy barrier than unimolecular decomposition of glucose.…”
Section: Cellulose Pyrolysismentioning
confidence: 99%
“…Indeed, the chemical aspect of biomass fast pyrolysis can be described as a combination of parallel and successive reactions of a nonionic and ionic nature 13. If radical mechanisms are invoked and are predominant in coal pyrolysis,14 recent experimental evidence6, 7, 15 and theoretical calculations16, 17 for biomass fast pyrolysis suggest the predominance of nonionic reactions during the primary pyrolysis stage. This ongoing discussion on the importance and predominance of the ionic and/or nonionic character of fast pyrolysis reactions13 has provided important clues that have not yet been used to rationalize the degradation modes.…”
Section: Introductionmentioning
confidence: 99%